Pengaruh Brand Ambassador dan Brand Image Terhadap Purchase Intention Pada Azarine Cosmetic di Kota Malang - Ajeng Puspita Maharani; Achmad Zaini; Asminah Rachmi (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The increasingly intense competition in the cosmetics industry has encouraged local brands such as Azarine Cosmetic to implement innovative marketing strategies, including the use of brand ambassadors and the development of a strong brand image. However, previous studies on the influence of these two variables on purchase intention have shown varying results, creating a research gap, particularly in the context of Malang City. This study aims to determine the effect of brand ambassador and brand image on the purchase intention of Azarine Cosmetic sunscreen products in Malang City, both partially and simultaneously. This research employs a quantitative approach with an explanatory research design. Data were collected through an online questionnaire distributed to 100 respondents who were familiar with Azarine Cosmetic products and recognized Prilly Latuconsina as the brand ambassador, using purposive sampling technique. The data were analyzed using multiple linear regression and hypothesis testing. The results indicate that both brand ambassador and brand image have a significant effect on purchase intention, both partially and simultaneously.